Rare Exome Sequence Variants in CLCN6 Reduce Blood Pressure Levels and Hypertension Risk. (February 2016) - Yu, Bing; Pulit, Sara L.; Hwang, Shih-Jen; Brody, Jennifer A.; Amin, Najaf; Auer, Paul L.; Bis, Joshua C.; Boerwinkle, Eric; Burke, Gregory L.; Chakravarti, Aravinda; Correa, Adolfo; Dreisbach, Albert W.; et al.
Abstract : Background—: Rare genetic variants influence blood pressure (BP). Methods and Results—: Whole-exome sequencing was performed on DNA samples from 17 956 individuals of European ancestry and African ancestry (14 497, first-stage discovery and 3459, second-stage discovery) to examine the effect of rare variants on hypertension and 4 BP traits: systolic BP, diastolic BP, pulse pressure, and mean arterial pressure. Tests of ≈170 000 common variants (minor allele frequency, ≥1%; statistical significance, P ⩽2.9×10 −7 ) and gene-based tests of rare variants (minor allele frequency, <1%; ≈17 000 genes; statistical significance, P ⩽1.5×10 −6 ) were evaluated for each trait and ancestry, followed by multiethnic meta-analyses. In the first-stage discovery, rare coding variants (splicing, stop-gain, stop-loss, nonsynonymous variants, or indels) in CLCN6 were associated with lower diastolic BP (cumulative minor allele frequency, 1.3%; β =−3.20; P =4.1×10 −6 ) and were independent of a nearby common variant (rs17367504) previously associated with BP. CLCN6 rare variants were also associated with lower systolic BP ( β =−4.11; P =2.8×10 −4 ), mean arterial pressure ( β =−3.50; P =8.9×10 −6 ), and reduced hypertension risk (odds ratio, 0.72; P =0.017). Meta-analysis of the 2-stage discovery samples showed that CLCN6 was associated with lower diastolic BP at exome-wide significance (cumulative minor allele frequency, 1.1%; β =−3.30; P =5.0×10 −7 ). Conclusions—: These findings implicate the effect of rare coding variants in CLCN6 in BP variation and offer new insights into BP regulation. Abstract : Supplemental Digital Content is available in the text.